Evaluating the Design of Behavior Change Interventions: A Case Study of Rhino Horn in Vietnam - and Olmedo, Alegría; Sharif, Vian; Milner-Gulland, E. J. (Conservation Letters, 2018)
Behavioral change interventions are increasingly widely used in conservation. Several projects addressing rhino horn consumption were recently launched in Vietnam. We used key informant interviews, document analysis, and marketing theory to explore their strategies for intervention design, implementation, monitoring, and evaluation. We developed a framework to evaluate whether they followed best practice and identify implementation challenges. Interventions could make greater use of key project design steps, including basing interventions on robust research to understand the behavior in question, identifying the target audience whose behavior interventions aim to change, and developing measures that can provide reliable evidence of success or not. Challenges include the need for law enforcement to complement campaigns; improving cooperation between NGOs; and clearly defining aims of demand-reduction initiatives. Using best practice from other fields and considering demand reduction within the wider context of wildlife, trade policy will help address these challenges.
Keywords: Awareness; Ilegal wildlife trade; Project design; demand reduction; social marketing